Pregnancy, maternal tobacco smoking and early age leukemia in Brazil - Koifman, Sergio (Frontiers in Oncology, 2012)
Background: Cigarette smoking has been associated with acute myeloid leukemia but hypothesis on the association between maternal smoking during pregnancy and childhood leukemia is unclear. Objectives: To investigate the association between maternal exposure to tobacco smoking during pregnancy and early age (< 2 yr.) leukemia (EAL). Methods: A hospital-based multicenter case-control study aiming to explore EAL risk factors was carried out in Brazil during 1999-2007. Data were collected by direct interview with the biological mothers using a standardized questionnaire. The present study included 675 children, being 193 acute lymphoblastic leukemia (ALL), 59 acute myeloid leukemia (AML), and 423 controls, being the latter age frequency matched and paired by area of residence with the cases. Unconditional logistic regression was performed, and odds ratios (OR) on the association between tobacco smoking (3 months before pregnancy, during pregnancy, and 3 months after delivery) and EAL were ascertained after adjustment for selected variables (maternal age at birth and education, birth weight, infant skin color, and oral contraceptives use during pregnancy).Results: Smoking was reported by 17.5% of case mothers and 20.6% of controls´. Among women who reported to have smoked 20 or more cigarettes during the index pregnancy, an adjusted OR = 5.28 (95% C.I. 1.40-19.95) for ALL was observed. Heavy smoking during breastfeeding yielded an adjusted risk estimate for ALL, OR = 7.78 (95% C.I. 1.33-45.5). No dose-response effect was observed according to smoking exposure during pregnancy and EAL. An association between secondhand smoking during pregnancy or breastfeeding was not observed. Conclusion: An association between maternal smoking and AAL in the offspring was restricted to women who have reported an intense exposure to tobacco smoke during pregnancy and breastfeeding.